OPTIMASI JUMLAH TENAGA KERJA BERDASARKAN WAKTU STANDARD - Sitorus, Erwin; Alfath, Nurhikmah (Jurnal Sistem Teknik Industri, 2017)
The most important components in the company are human resources. The use of human resources is not optimal it may cause losses by companies and labor. If the amount of labor is too little, it will cause the buildup at the work station. If the labor too much, it will cause losses due to waste. In this company, the process of producing cigarette paper is divided into three main phases, namely preparation stage , the process of making paper and the finishing stages. The process of producing activities cigarette paper needs human resources optimally. The problems that arise during production process activities are the use of human resources that are not optimal, resulting in the shortage of labor and labor surplus work that is working on the work that is stacking. This study was conducted to determine when the standard work and can provide a good decision in the optimal amount of labor on the packaging of ream paper products form. Results resulting from the standard time of each element ie the element wrapping cigarette paper sheet with a standard time of 177.79 seconds, enter the box packaging packaging with the standard time, 119.20 seconds, full box with a standard price of 231.15 seconds and wrap the packaging using plastic with a standard time of 55.31 seconds. The total labor standard packaging process with the method of data as much as 15 people / shift seconds actual workforce of 13 people. Enough amount of labor as much as 2 people.